Enhancing the ISIS‐I Topside Digital Ionogram Database. Issue 12 (15th December 2018) - Benson, Robert F.; Bilitza, Dieter; Fung, Shing F.; Truhlik, Vladimir; Wang, Yongli
Abstract: Selected original analog telemetry tapes from three of the topside‐sounder satellites of the International Satellites for Ionospheric Studies (ISIS) program, namely Alouette 2, ISIS I, and ISIS II, were used in an earlier project to produce more than ½ million digital topside ionograms; the resulting digital topside ionograms from ISIS II were used to produce more than 86, 000 globally distributed vertical topside ionospheric electron density profiles Ne (h) that cover a time span of more than a solar cycle. These Ne (h) were produced using the Topside Ionogram Scaler with True height algorithm auto‐scaling software. Before attempting to automatically process Alouette‐2 or ISIS‐I ionograms, a data‐enhancement project was initiated so as to increase the number of ionograms suitable for manual scaling and to increase the auto‐processing success rate. These enhancements were mainly to correct problems that often occurred during the analog‐to‐digital conversion of the original telemetry tapes. Here we illustrate the improvements made to the ISIS‐I digital topside ionograms and compare Ne values at the satellite altitude and Ne (h) profiles, based on the manual scaling of selected ionograms, to both the auto‐scaled values and the predictions of the International Reference Ionosphere 2016 model. The results indicate the need to improve the available auto‐processing software for the new ISIS‐I digital ionograms and that International Reference Ionosphere 2016 predicts midlatitude winter topside Ne values that are too high in the late morning and at noon but too low in the early morning. Plain Language Summary: Data from the Alouette/ISIS topside‐sounder satellites from the 1960s and 1970s still provide some of the most useful information on the topside ionosphere on a global scale. This region, that is, above the electron density peak near 300‐km altitude, is not very well represented by ionospheric models, yet it has a significant impact on advanced technological systems, such as navigation, that depend on radio signals that traverse the entire ionosphere. This study builds on earlier investigations and uses the latest digital files from the International Satellites for Ionospheric Studies‐I satellite to demonstrate the importance of these files, the challenges encountered in developing software to automatically process them, and to indicate regions where the International Reference Ionosphere model is in need of improvement. Key Points: ISIS‐1 digital topside ionogram database enhancements enable more efficient manual scaling and automatic processing Manual scaling indicates the need for improvements in existing automatic‐processing software for ISIS‐1 digital topside ionograms The new ISIS‐1 ionograms are valuable for improving the International Reference Ionosphere model in the topside ionosphere